SORPTION OF Pb(II), Cu(II) AND Cd(II) BY BIOMASS OF THE DIFFERENT ACTIVATED SLUDGE - Nguyễn, Đình Trung (2022)
AbstractBiomass of digested sludge and resting sludge can be easily applied as a cheap bio-adsorbent for heavy metal ions such as Pb2+, Cu2+ and Cd2+. Langmuir model was found to fit the experimental adsorption and desorption data of the heavy metal on to the biomass of sludge. That has the competition uptake between the difference metal with another when the adsorption system has the di-metal, and tri-metal combination. The maximal adsorption capacity of resting sludge was 0.517 mM Pb2+/g; 0.552 mM Cu2+/g; 0.389 mM Cd2+/g, and the maximal adsorption capacity of the digested sludge was 0.478 mM Pb2+/g, 0.43 mM Cu2+/g and 0.549 mM Cd2+/g. In the absorption system, it was found that, di-metal combine such as (Cu2+ - Cd2+), (Pb2+ Cd2+), and (Cu2+ - Pb2+), the metal uptake Cu2+ ≈ 3Cd2+, Pb2+ > 3Cd2+, and Cu2+ ≈ Pb2+ respectively. When tri-metal Cu2+ - Cd2+ - Pb2+ combines the number of complex formation varies in the following order: Pb2+ > Cu2+ > Cd2+. Extracellular polymeric substances (EPS) were extracted by sonication method. Humic substances were greater than protein and polysaccharide for digested sludge, for resting sludge the protein is greater than humic. The ratio protein/polysaccharide varies from 1.25 to 2.7, this ratio is highest for resting sludge. Affinity absorption of Cu2+ and Pb2+ was higher than Cd2+, that have the competition metal uptake with functional groups such as hydroxyl, carbonyl, amide on the biomass surface of the sludge.